PENDEKATAN BUDAYA DALAM HARMONISASI RELASI MUSLIM DAN NON MUSLIM - Surya Adi Sahfutra (IBDA` : Jurnal Kajian Islam dan Budaya, 2012)
This paper reveals about the life of Islam and its interaction withreligious believers in the Turgo Village on the slopes of Merapi. Turgosociety living in harmony, which is built on the collective cultural values.Between residents of different religions established communication andinteraction are active in various aspects of community life, such as environmentalconservation, social and religious interaction, and cultural actionundertaken jointly with models of their own religion. Harmony inthe society due to cultural aspects are preferred in communication andinteraction patterns in the life of a pluralistic rather than the religiousaspect. That is, in the public space, culture plays an important role inorder to create harmony.